AN ANALYSIS OF FACTORS AFFECTING AUDIT DELAY IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Mahanani, Setyo; Yusoff, Mohd Nor Hakimin; Abdullah, Tahirah; Sidik, Mohamad Hazeem Mohmad; Hadi, Nor; Adrianto, Teguh Widodo (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
Timely financial reporting is essential for maintaining investor confidence and ensuring efficient capital market performance. Audit delay between a company’s fiscal year-end and the issuance of its audited financial statements remains a critical issue, particularly in emerging markets like Indonesia. This study investigates the effect of Public Accounting Firm (PAF) size, profitability, liquidity, and asset activity on audit delay in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Using purposive sampling, a sample of 135 companies was selected, resulting in 405 observations of panel data. The analysis was conducted using regression with the Random Effects Model (REM) via EViews 12 software. The findings reveal that profitability has a negative and significant effect on audit delay, suggesting that more profitable firms tend to receive quicker audit completion. In contrast, PAF size, liquidity, and asset activity do not show a significant influence on audit delay. This research contributes to the literature by focusing on the manufacturing sector which deemed as an essential pillar of Indonesia's economy and by employing recent data and robust statistical methods to deepen the understanding of audit timeliness in emerging market contexts.